Human Resource Accounting Information: A Comment Concerning Demand Characteristics. - Snowball, Doug (The Accounting Review, 1979)
Few individuals presently can claim genuine familiarity with HRA data. Professor of Accounting J.A. Hendricks confined his analysis to subjects who indicated an understanding of the meaning of HRA. Yet, it is likely that most had never seen statements containing such data prior to the experiment; indeed, the subjects had read and heard little about the topic. As a result, their perceptions of the characteristics of the data (e.g., perceptions of the data's objectivity, reliability and, most importantly, relevance) must have been formed primarily on the basis of the materials presented in the experiment. How they perceived the HRA data is unclear. The only reasonably safe assumption that can he made is that the data were perceived to be novel. It may be argued that the subjects' responses bear some relationship to the reactions of "real world" investors to the initial introduction of HRA statements. However, "real world" decisions have economic consequences and reactions to novel data in such an environment are likely to be very different (e.g., more cautious) than those in an experimental situation. The more important issue, though, is the impact of HRA data presented on a continuing basis; the responses of Hendricks's subjects offer no insight into either experimental or "real world" reactions once such data lose their novelty.